Techno-economic study of a hybrid power generation system at the Lebanese coastal highways - Mohammad Hammoud; Jaafar Hallal; Tala Moussa; Hussein Kassem (Institute of Advanced Engineering and Science, 2021)
Despite its great importance in daily life, electricity remains one of the most critical issues in Lebanon where the power supply has been erratic for years and the government faces numerous problems in buying foreign currency for fuel import from petroleum countries. Therefore, there is an urgent need for efficient solutions to produce local energy in a more sustainable way, leading to an environmentally friendly energy consumption, far away from conventional energy sources. In this work, unconventional technologies are used for the generation of clean energy from a system of photovoltaic (PV) panels and wind turbines. The novelty lies in the fact that the cost of the land required for the installation is almost zero. The middle of the highways is usually left unoccupied and therefore suitable for the project. Another innovative feature of the proposed system is its ability to be connected to the public utility without the need for battery storage, which reduces the total cost of the system. The proposed design consists of 87,750 PVs arranged in pairs on a steel frame for a coastal distance of 117,000 meters (highway distance between Tyre and Tripoli) with a width of 2 meters and 29,250 vertical wind turbines placed under the chassis. Using RETScreen software, the capacity of the resulting system is estimated at 39.9 GW/year. The system would lead to a reduction in CO2 and GHG emissions of approximately 28,211 tCO2/year. The payback period of this project is estimated at 9 years with a lifetime of 25 years.